Correlates of Adverse Childhood Experiences (ACES), Emotional Regulation, and Self-Esteem among In-School Adolescents in Ibadan, Nigeria - Ogunbowale, Ibidunni Abifoluwa; Adebola, Olatinwo Elizabeth; Umanhonlen, Sylvester Ehimare; Oyetola, Adewole Funmilayo (NIU Journal of Humanities; Vol 10 No 1 (2025): NIU Journal of Humanities, Vol. 10 No. 1, March 2025, 2025)
The study examined the effects of adverse childhood experiences on low self-esteem and difficulties in emotional regulation among in-school adolescents in Ibadan, Oyo State, Nigeria. A descriptive survey design was used with a target population of 13- to 19-year-old adolescents selected through a three-stage random sampling technique. The sample comprised 300 adolescents, which consisted of 100 randomly selected participants from each of the three randomly chosen local government areas. Data were subjected to adapted scales measuring ACEs, self-esteem, and emotional regulation difficulties, including the ACEs scale, Rosenberg Self-Esteem Scale, and the Emotion Regulation Questionnaire; all had good reliability. The descriptive and inferential statistics such as Pearson's Product Moment Correlation and Multiple Regression Analysis were used to test the relationships and contributions of ACEs to the psychological outcomes. Findings are expected to open up new insights into how adverse childhood experiences psychologically affect affected adolescent students while further guiding the development of interventions in educational settings. Keywords : Adverse Childhood Experiences (ACEs), Self-esteem, Emotional regulation, In-school adolescents